Training and Qualifying the Mufti to Address Contemporary Jurisprudential Developments and the Role of Religious Institutions in It - Alawi, Asst Prof. Dr. Mahmoud Rahim Alawi (Sulaimani Journal for Humanities, 2026)
The abundance of new developments in our contemporary life necessitates and compels religious institutions to produce well-qualified muftis who are capable of providing appropriate solutions to the increasing number of emerging issues and urgent matters that arise in our society, which continues to expand with the changes in time and place. Islamic Sharia has, since its inception, paid great attention to this matter to keep pace with the rapid changes in Muslims' lives and the expansion and spread of Islam. Thus, various jurisprudential and fatwa schools emerged in the Islamic regions, from Madinah and Hijaz to Kufa, Basra, and other cities — this was in the early Islamic period. In our time, which witnesses tremendous developments in modern technology and innovations, accompanied by emerging issues in various fields such as economics, financial transactions, medicine, and others, it has become necessary for religious and legal institutions to adopt an active role in addressing these contemporary issues and strive to find suitable solutions in line with the principles of Sharia and religious values. This research aims to provide a foundational and practical study on the preparation and qualification of the mufti, and to clarify the role of religious institutions in enabling the mufti to perform his function effectively in confronting contemporary jurisprudential developments.
Keywords: Mufti training; Mufti qualification; jurisprudential developments; contemporary jurisprudence; role of religious institutions